ANALISIS TERHADAP MUATAN INTEGRASI KEILMUAN DALAM MATERI PERKULIAHAN PADA PROGRAM STUDI HUBUNGAN INTERNASIONAL UIN ALAUDDIN MAKASSAR - Nur Aliyah Zainal; Zulfiani Masud (Review of International Relations, 2021)
After the transition from IAIN (Institut Alauddin Islam Negeri) to UIN (State Islamic University), Alauddin State Islamic University Makassar formed a general scientific study department /program that is adjacent to other religious studies. The department has consequences for integrating its knowledge with Islamic studies. This research then questioned about the concept of Scientific Integration UIN Alauddin Makassar and how the content of scientific integration in RPS of  Department of  International Relations. And the results of the study showed that UIN Alauddin Makassar Scientific Integration Concept that tends to be fickle so that until now has not implemented a definite and clear as in UIN Sunan Kalijaga and UIN Maulana Malik Ibrahim. Then,the scientific integration in the Semester Learning Plan (RPS) in the International Relations Study Program was minimally found the concept of integration. This is related to literature that is also minimal  and examine the theory or concept in International and Islamic Relations, so that in the application of scientific integration, especially in the International Relations Study Program itself is still lacking in the content of lecture materials. Keywords: Scientific Integration, Semester Learning Plan, International Relations Programe